Innovation To Change Student Behavior At School Has An Influence The Value Of The Traditional Game Philosophy Of Gobak Sodor - Parengkuan, Meyke (Physical Education Departement of University PGRI Jombang, 2024)
The very rapid development of technology causes problems with changes in societal conditions which include social, economic and lifestyle problems. Technological changes that are not balanced with good thinking and understanding will result in changes to the understanding of social interactions in the social environment. Situations like this will have an impact on children's behavior and even movement activities at school. Promiscuity and juvenile delinquency still occur very often in Indonesia. Playing is a form of experience that must be experienced, through playing activities children will create an experience that can help develop physically, emotionally and socially. Paying attention to this, it is very necessary to find innovation, so that students experience changes in behavior. In students, changes in technology and the rapid development of the times are one of the causes of changes in behavior and influence the philosophy in the game Gobak Sodor. The method used in the research is a descriptive qualitative method, analyzing facts regarding the existence of traditional games and the values in Gobak Sodor. The subjects in this research were physical education teachers in junior high schools states in Tuban regency. The results of the research explain that Gobag Sodor is a traditional game that can be a source of values that can shape student behavior, and a form of cultural values in society, as well as the learning process at school.